Determination of the spinel group end-members based on electron microprobe analyses - Ferracutti, Gabriela Roxana (2014)
The spinel group minerals have been the focus of many studies, not only because of their economic interest, but also due to the fact that they are very useful as petrogenetic indicators. The application End-Members Generator (EMG) allows to establish, based on electron microprobe analyses (EMPA), the 19 end-members of the spinel group: MgAl2O4 (Spinel sensu stricto, s.s.), FeAl2O4 (Hercynite), MnAl2O4 (Galaxite), ZnAl2O4 (Gahnite), MgFe2O4 (Magnesioferrite), Fe3O4 (Magnetite), MnFe2O4 (Jacobsite), ZnFe2O4 (Franklinite), NiFe2O4 (Trevorite), MgCr2O4 (Magnesiochromite), FeCr2O4 (Chromite), MnCr2O4 (Manganochromite), ZnCr2O4 (Zincochromite), NiCr2O4 (Nichromite), MgV2O4 (Magnesiocoulsonite), FeV2O4 (Coulsonite), MnV2O4 (Vuorelainenite), Mg2TiO4 (Qandilite) and Fe2TiO4 (Ulvöspinel). EMG is an application that does not require an installation process and was created with the purpose of performing calculations to obtain: cation proportions (per formula unit, p.f.u.), end-members of the spinel group, redistribution proportions for the corresponding end-members in the Magnetite prism or Ulvöspinel prism and a data validation section to check the results. EMG accepts .csv data files and the results obtained can be used to represent a given dataset with the SpinelViz program or any other 2D and/or 3D graph plotting software.